2014
DOI: 10.1016/j.clp.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Antagonist Therapy for Retinopathy of Prematurity

Abstract: Synopsis In this article we discuss the growing problem of ROP worldwide, treatments for severe ROP including standard of care laser treatment, and the need for new treatments. We will also discuss the reasons to consider inhibiting the VEGF signaling pathway in severe ROP and the concerns about broad VEGF inhibition. Finally, we will cover the potential role of VEGF in ROP based on studies in animal models of oxygen-induced retinopathy (OIR), the effects of anti-VEGF based on basic research data, and the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 80 publications
2
49
1
1
Order By: Relevance
“…1 Tüm dünyada hem gelişmiş hem de gelişmekte olan ülkelerde çocukluk çağındaki önlenebilir körlüğün en önemli sebebini oluşturan PR, şimdiye kadar dünya genelinde yaklaşık 50.000 çocukta kalıcı görme kaybına neden olmuştur. 2 Gelişen teknolojik ve yenidoğan yoğun bakım üniteleri (YYBÜ) imkanları yardımıyla yaşatılabilen prematüre bebeklerin sayısı arttıkça prematüriteye bağlı komplikasyonların dolayısıyla PR'nin sıklığı da artmıştır.…”
unclassified
“…1 Tüm dünyada hem gelişmiş hem de gelişmekte olan ülkelerde çocukluk çağındaki önlenebilir körlüğün en önemli sebebini oluşturan PR, şimdiye kadar dünya genelinde yaklaşık 50.000 çocukta kalıcı görme kaybına neden olmuştur. 2 Gelişen teknolojik ve yenidoğan yoğun bakım üniteleri (YYBÜ) imkanları yardımıyla yaşatılabilen prematüre bebeklerin sayısı arttıkça prematüriteye bağlı komplikasyonların dolayısıyla PR'nin sıklığı da artmıştır.…”
unclassified
“…Animal models of oxygen-induced retinopathy (OIR) studies have shown vascular endothelial growth factor (VEGF) to be a key player in the pathogenesis of ROP 3. This has resulted in clinicians using intravitreal anti-VEGF to treat ROP 4. In a recently published Cochrane Systematic Review titled ‘Anti-vascular endothelial growth factor (VEGF) drugs for the treatment of retinopathy of prematurity’, the authors evaluated data from three clinical trials, in which 239 premature infants were participated 5.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that factors which protect the foetus from development of severe ROP include elevated anti-angiogenic factors in maternal blood may pass through the placenta to enter foetal circulation or anti-angiogenic factors in amniotic fluid may be absorbed through cornea into retina of the foetus or there may be genetic tendency of the foetus to produce more antiangiogenic factors (sFlt1, sEng) in response to hypoxia, 8 both in the placenta (foetal tissue) and the retina.…”
Section: Future Scope Of Our Studymentioning
confidence: 99%